Changes in functional traits of Piper reticulatum (Piperaceae) leaves under light and shade in La Selva, Costa Rica (UNED Research Journal, 2020)
Introduction: Plants are exposed to environments with different light availability, and light is the major limiting factor in tropical rainforests. In response, leaves modify their functional traits to exploit available light and avoid hydric stress. However, how plants change their functional traits in different light conditions remains poorly understood. Objective: This study concentrates on the adaptation of Piper reticulatum (Piperaceae) leaves in different light environments. Additionally, the study investigates whether these changes occur in the leaves’ young or mature stages. Methods: Sixty leaves (one young and one mature per individual) were collected from a total of 30 P. reticulatum individuals in La Selva Biological Station, Costa Rica, 15 individuals were in the shade and 15 individuals were exposed to direct sunlight. The leaf area and specific leaf mass of each leaf was measured to record differences in biomass allocation. Additionally, the stomata and tertiary veins of each leaf were counted to determine whether there are adaptations against dehydration in environments with more light. Results: Sunlit leaves had a higher number of stomata, fewer tertiary veins, and higher specific leaf mass. Furthermore, younger leaves showed more stomata but lower specific leaf mass. Conclusions: Plants under different light conditions differed in stomata, veins and mass, and leaf age was a factor.
Keywords: leaf area; ontogeny; stomas; specific leaf mass; plasticity